Management of Adverse Effects in Testosterone Replacement Therapy - Basheer Basheer; Vishal Ila; Rodrigo Barros; Francesco Mesquita; Leonardo Seligra Lopes; Victor Fernandes Negris Lima; Luciano A. Favorito; Ranjith Ramasamy (International Brazilian Journal of Urology)
ABSTRACT Purpose: This narrative review aims to provide the most updated knowledge regarding the treatment of adverse effects secondary to testosterone replacement therapy (TRT), such as gynecomastia, cardiovascular and hematologic risks, prostate health risk, and liver dysfunction risks. Materials and Methods: An extensive literature review was conducted, incorporating guidelines from the American Urological Association and the Endocrine Society. The studies determined common adverse effects and their most common methods of management. Results: TRT improves the quality of life, sexual function, and mood in hypogonadal men. Possible adverse effects associated with TRT include increased estrogen levels and gynecomastia, which are usually managed with aromatase inhibitors and tamoxifen. Cardiovascular risks from TRT include hypertension and erythrocytosis, which mandate periodic hematocrit and blood pressure monitoring; therapeutic phlebotomy is indicated if the hematocrit exceeds 52%. No significant concern regarding prostate cancer has been observed in the closely monitored patient. However, TRT should not be administered to individuals with active evidence of untreated prostate cancer, except under rare circumstances such as active surveillance for very low-risk disease. Older oral forms of TRT can affect liver function; therefore, transdermal, newer oral forms and injectables are generally favored in men with a history of liver disease. Conclusions: Monitoring and management of adverse effects are critical to maximize benefit and minimize the risks of TRT. Ongoing research will further elucidate the safety of TRT while advancing evidence-based practices in managing its associated adverse effects. Effective patient education and counseling are also essential to improve compliance and treatment outcomes.